2016
DOI: 10.1111/ejn.13409
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term progressive motor skill training enhances corticospinal excitability for the ipsilateral hemisphere and motor performance of the untrained hand

Abstract: It is well-established that unilateral motor practice may cause increased performance in the opposite nontrained hand. Here, we test the hypothesis that progressively increasing task difficulty during long-term skill training with the dominant right hand increase performance and corticomotor excitability of the left non-trained hand. Subjects practiced a visuomotor tracking task engaging right digit V for 6 weeks with either progressively increasing task difficulty (PT) or no progression (NPT). Corticospinal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
3
14
1
Order By: Relevance
“…The current results provide proof-of-concept that long-term (6 weeks) of progressive practice leads to better performance on a task level with high demands for accuracy and speed compared to non-progressive practice. The present results are in line with our previous findings that progressive practice facilitates skill acquisition for both the trained and untrained hand after 4 days and 6 weeks of training, respectively 4,11 . While the small number of participants tested on the high level of task difficulty (n = 12, 6 in each group) calls for a cautious interpretation, the difference between participants depicted in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current results provide proof-of-concept that long-term (6 weeks) of progressive practice leads to better performance on a task level with high demands for accuracy and speed compared to non-progressive practice. The present results are in line with our previous findings that progressive practice facilitates skill acquisition for both the trained and untrained hand after 4 days and 6 weeks of training, respectively 4,11 . While the small number of participants tested on the high level of task difficulty (n = 12, 6 in each group) calls for a cautious interpretation, the difference between participants depicted in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Progressive practice leads to superior performance. In the present study, we adapted a task previously used over a similar timespan 11 . This task enables individually adjusted requirements for motor acuity (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in CSE can be modulated by changes in SICI (Kidgell et al 2013); however, given that NPST had no effect on ipsilateral CSE, it is not surprising that there were no changes in SICI. In addition, it has recently been shown that motor training that is progressively challenging, such as visuomotor tracking and SPST, leads to greater levels of cortical plasticity when compared to non-progressive motor-skill training (Christiansen et al 2017). In this current study, both the visuomotor training and SPST protocol involved progressive overload compared to NPST and a greater number of sensory cues (visual and auditory), and these factors alone may account for the changes in CSE.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upmentioning
confidence: 73%
“…SICI is a standard method used to estimate the excitability of cortico-cortical circuits within the M1 that uses GABAA neurotransmission (Rothwell et al 2009). Many plasticity-inducing interventions, such as motor-skill training (Liepert et al1998) and strength training (Weier et al 2012;Leung et al 2017), show that the removal of SICI is an important mechanism for optimal motor-skill learning (Christiansen et al 2017). Cross-education of motor performance studies, including acute (Perez and Cohen 2008;Howatson et al 2011) and chronic studies (Goodwill et al 2012;Kidgell et al 2015) that have examined SICI, have reported reduced SICI in the M1 ipsilateral to the training limb.…”
Section: The Cortical Adaptations To Cross-education Are Dependent Upmentioning
confidence: 99%
See 1 more Smart Citation